Are service-delivery NGOs building state capacity in the Global South? - Bukenya, Badru (John Wiley & Sons, 2017)
Service-delivery NGOs are often attacked for abandoning the pursuit of ‘alternative development’ in favour of ‘technocratic’ forms of development. Yet some commentators argue that these organizations can have progressive impacts on political forms and processes. We investigate this debate through the lens of state building. Research into The AIDS Support Organisation's (TASO) work with the Ugandan government reveals that its state capacity building effects were both uneven and temporary. Although TASO played important roles in strengthening the bureaucratic ability of targeted hospitals to deliver HIV/AIDS services and increased the state's embeddedness in society in the targeted districts, it was less successful in expanding the infrastructural reach of the state in rural Uganda. We conclude that NGOs need longer time-frames to achieve state building goals.
Experiences from HIV/AIDS programmes in rural Uganda
Keywords: Service-delivery; NGO; HIV/AIDS; Rural Uganda; Global South